Les rapports psychanalyse et autobiographie : dans les lignes et entre les lignes - Adela Abella (Temporalités)
Drawing on the autobiographies written by twelve “difficult” pupils, the author discusses two psychoanalytical paradigms that are currently used today. The archaeological paradigm, whose aim is to unveil the latent under the manifest, pertains to a logic pointing towards the past. On the other hand, the transformative paradigm, which seeks to foster the development of “psychic muscles”, is more akin to the idea of a plurality of possibilities located in the future. The author suggests the need to combine dialectically both paradigms in clinics and in the approach of cultural phenomena, including autobiographies. The ethical problems linked to the intervention of the analyst/interpreter are central.